2015
DOI: 10.1017/s0007114515002846
|View full text |Cite|
|
Sign up to set email alerts
|

Rapid increase in fibroblast growth factor 21 in protein malnutrition and its impact on growth and lipid metabolism

Abstract: Protein malnutrition promotes hepatic steatosis, decreases insulin-like growth factor (IGF)-I production and retards growth. To identify new molecules involved in such changes, we conducted DNA microarray analysis on liver samples from rats fed an isoenergetic low-protein diet for 8 h. We identified the fibroblast growth factor 21 gene (Fgf21) as one of the most strongly up-regulated genes under conditions of acute protein malnutrition (P < 0·05, false-discovery rate <0·001). In addition, amino acid deprivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Therefore, we tested the possibility that endocrine Fgf21 from the liver regulates the development of thymocytes. To examine this possibility, we adopted a protein-free diet (PF), which was separately reported to induce upregulation of serum Fgf21 and alter cellularity of thymocytes 24, 25 . Three-week-old WT and Fgf21 KO male mice were fed with PF for 1 week.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we tested the possibility that endocrine Fgf21 from the liver regulates the development of thymocytes. To examine this possibility, we adopted a protein-free diet (PF), which was separately reported to induce upregulation of serum Fgf21 and alter cellularity of thymocytes 24, 25 . Three-week-old WT and Fgf21 KO male mice were fed with PF for 1 week.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we examined whether endocrine Fgf21 could regulate thymopoiesis under physiological conditions. To induce endocrine Fgf21 from the liver, we preliminarily tested several metabolic stresses such as fasting, drinking sucrose water, high-fat diet, and PF 24, 3134 . Among these stresses, PF could induce the highest level of endocrine Fgf21, and only PF could alter the percentage of CD4SP and CD8SP cells accompanied by decreased cellularity as shown in FTOC with FGF21 (Figs 6, 8 and S5).…”
Section: Discussionmentioning
confidence: 99%
“…Since FGF21 is induced by both high and low carbohydrate diets, the view is that FGF21 is not regulated by carbohydrates alone but also by the reduction in protein [86]. Feeding a low-protein (5% casein) isoenergetic diet (vs. 15%-20% casein in the control diet) either short-term (8 h) in rats or longer-term (5-11 days) in mice led to an upregulation of FGF21 gene expression in the liver and an increase of FGF21 levels in plasma [87]. In humans, restricting dietary protein for 28 days caused plasma FGF21 to rise [86].…”
Section: Proteins (Low-protein Diet Methionine-or Leucinerestricted mentioning
confidence: 99%
“…While FGF21 was originally discovered as a liver-enriched FGF [8], it was subsequently shown to be a non-mitogenic metabolic regulator with therapeutic potential for obesity-related-metabolic dysfunction [9], [10], [11], [12], [13], [14], even in humans [15], [16]. More recently, the physiological context of FGF21 has been increasingly explored [17], [18], [19], with several studies from diverse laboratories now having shown that it is an endocrine signal of dietary PD in rodents [5], [20], [21], [22], [23], [24], [25] and in humans [5], [21], [26], [27]. While the downstream mechanisms by which FGF21 improves metabolic health with dietary PD are yet to be fully resolved, it is required for increased energy expenditure, at least in mouse models [5], [21], [22], and heightened energy expenditure is thought to be a promising strategy to combat obesity-related-metabolic disease [28].…”
Section: Introductionmentioning
confidence: 99%